Impact of COVID-19 on Educational Planning in Federal Capital Territory, Abuja, Nigeria. - Ogunode Niyi Jacob; Jegede Deborah; Audu Elizabeth I; Adah Samuel (Universitas Syiah Kuala, 2021)
This study investigated the impact of COVID-19 on educational planning in Federal Capital Territory, Abuja. Adopted for this study was descriptive survey research design by the researchers. The population of the study comprised all educational planners in federal Capital Territory, Abuja. The sample for the study was 120 educational planners selected from 10 educational institutions handling planning of education in the Territory. The sample was drawn through randomly and proportionate random sampling techniques. The researchers used self-developed instrument. A four point adapted Likert-scale of measurement was used thus: Strongly agree (SA), agree (SA), disagree (D), strongly disagree (SD). The reliability of the instrument was established through test-retest method. The responses of the respondents were presented in simple statistical table and analysed using Mean (x̅) and Standard Deviation. In taking decision on the research questions, mean scores for 2.50 and above were deemed as agreed, accepted or positive while those below 2.50 were regarded as negative and unaccepted/disagreed responses. The result obtained shows that Covid-19 have affected educational planning in Federal Capital Territory, Abuja, planning hours were affected as a result of early closure of educational institutions across the Nation, majority of planners in Nigeria lack e-planning facilities to enable planners interact with their collogues and continue with planning processes during COVID-19, educational data on schools were unable to access it as a result of close down and poor implementation of planned programme could be attributed to covid-19 school closure or lockdown.